Estudo comparativo das análises cefalométricas manual e computadorizada - GUEDES, Priscila de Araújo (2013)
Objective: To conduct a comparative analysis between manual and computerized tracings using specific software, in order to define inter- and intraobserver results. Methods: A sample was used consisting of 50 standardized lateral cephalometric radiographs, of male and female patients of various age groups. The radiographs were analyzed by two observers, who each performed the manual and computerized tracings of all 50 radiographs. Angular and linear measurements were obtained, which were later submitted to the Mann-Whitney test in order to compare the inter- and intraobserver results between the two types of tracings. Results and Conclusions: the study concluded that confidence can be increased in tracings obtained from computer-assisted cephalometric analysis, as the discrepancies found between inter- and intraobserver tracings, both manual and computerized, were mostly not statistically significant.